PONDASI BALIK KOTAK DITANAH LUNAK - Sulardi, Sulardi; Widodo, Pria Agung; Suprayitno, Abdi; Ryka, Hamriani; Afifah, Rohima Sera; Waskita, Kukuh Jalu (INFO-TEKNIK, 2020)
The problem is the difficulty in determining the type and method of manufacture and installation of foundation on soft soils. The research objective is to provide an overview of the type of foundation, the method of manufacture and the method of installation of the foundation which is suitable and suitable in the soft soil environment. This research method uses used research methods with trial and error, and with a case study approach method, namely the case of difficulties in overcoming the problem of the availability of permanent structural support foundations and refinery operation equipment on soft soil. The results showed that the type and shape of the foundation that is suitable and to solve the problem is the foundation behind the box. This foundation specification is an inverted box with reinforced concrete material and certain dimensions with cover plates. The results of this used research also show that the inverted box type of foundation is suitable for supporting equipment supporting refinery operations such as pipe supports and other refinery operation equipment.